Determination of stability constants of mixed ligand complexes of cu(II) with creatinine and ethylenediamine tetra-acetic acid or I-glutamic acid: Potentiometric and spectrophotometric methods - (:unkn) unknown (Freund Publishing House Ltd, 2007)
Titration potentiometry and spectrophotometry have both been used to determine stability constants for mixed complexes of Cu(II) with creatinine and EDTA. Stability constants of the ternary system were evaluated by a method suggested by the Irving-Rossotti procedure. Conditional constants were established as a function of pH; the maximum values of the conditional formation constants were found to be in agreement with the mixed-ligand complex formation constants in a given pH region. The mole fractions of mixed complexes were calculated using the formation constants. The stability constants of mixed-ligand complexes at 25°C are: log K1 = 5.29, log K 2 = 4.97, with ionic strength being kept constant at I = 0.1 with NaClO4. Also, Cu(II)-I-glutamic acid-creatinine and Cu(II)-EDTA-creatinine complex formation, as examined by the spectrophotometric method, gave results that were in agreement with those of the potentiometric method.
Keywords: Copper(II) complexes; Creatinine; EDTA; I-glutamic acid; Mixed complex; Stability constants